2011
DOI: 10.5897/ajpp11.260
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial constituents from Morus nigra

Abstract: The objective of this study was to isolate and characterize the constituents of the local Morus nigra L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 12 publications
3
45
0
Order By: Relevance
“…Its root, twigs, bark and fruits contain phenolic compounds used to treat asthma. Studies have reported that the plant is rich in isoprenylated flavonoids, triterpenes and saponins, which have antioxidant, antibacterial and anticancer activities [6][7][8]. Ziziphus mauritiana (local name: Ber) is a fruit tree which belongs to family Rhamnaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Its root, twigs, bark and fruits contain phenolic compounds used to treat asthma. Studies have reported that the plant is rich in isoprenylated flavonoids, triterpenes and saponins, which have antioxidant, antibacterial and anticancer activities [6][7][8]. Ziziphus mauritiana (local name: Ber) is a fruit tree which belongs to family Rhamnaceae.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly as Black Mulberry (English) and Shah-toot (Hindi/Urdu). Pharmacologically it has been reported that M. nigra is anti-oxidant (Ozgenet al, 2009), anti-nociceptive (Padil-ha et al, 2009, anti-inflammatory (Padilha et al, 2010), antidiabetic (Husseinzadeh et al, 1999, anti-bacterial (Mazimba et al, 2011), cardiac depressant , effective for maternal health (Volpetoet al, 2011), vermifuge and anti-cancer (Kumar and Chauhan, 2008 Important phytoconstituents e.g. flavonoids, alkaloids and phenols have been reported in this plant Özgen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis, Micrococus flavus, Streptococcus faecal, Staphylococcus aureus, Eschericia coli, and Pseudomonas aeruginosa. 4,10 Previous studies showed that the ethanol extract of Morus nigra fruit has activity against Propionibacterium acnes (MIC 2.5 %) and Staphylococcus epidermidis (MIC 2.5 %).…”
Section: Introductionmentioning
confidence: 99%
“…There are several compounds that have been studied on Morus nigra L, such as fenol, flavonoid (kuwanon E and kuwanon U, and morusin), chalcone, 1-deoxynojirimycin. 3,4,5,6 Empirically in China, black mulberry plants are often used to decrease blood pressure, anti-hyperglycemic, diuretic, antioxidant, anthelmintic, anti-parasitic and antibacterial. 6,7,8,9 Black mulberry was known could inhibit bacterial i.e.…”
Section: Introductionmentioning
confidence: 99%